Hierarchical hollow Fe(2)O(3)@MIL-101(Fe)/C derived from metal-organic frameworks for superior sodium storage - Li, Chengping (Sci Rep, 2016)
A facile generic template-free strategy is employed to prepare hierarchical hollow hybrid Fe(2)O(3)@MIL-101(Fe)/C materials derived from metal-organic frameworks as anode materials for Na-ion batteries. The intrinsic hollow nanostructure can shorten the lengths for both electronic and ionic transport, enlarge the surface areas of electrodes, and improve accommodation of the volume change during Na(+) insertion/extraction cycling. Therefore, The stable reversible capacity of Fe(2)O(3)@MIL-101(Fe)/C electrode is 710 mAhg(−1), and can be retained at 662 mAhg(−1) after 200 cycles with the retention of 93.2%. Especially, its overall rate performance data confirm again the importance of the hierarchical hollow structures and multi-elements characteristics toward high capacities in both low and high current rates. This general strategy may shed light on a new avenue for fast synthesis of hierarchic hollow functional materials for energy storage, catalyst, sensor and other new applications.